Transformasi Pembelajaran PAI Melalui Pendekatan Berbasis Penyelidikan (Inquiry-Based Learning): Telaah Konseptual dan Implementatif - Dina; Marfit, Amirul Akbar; Kamal, Muhidinur (IIQ An Nur Yogyakarta, 2025)
The Inquiry-Based Learning (IBL) approach is a teaching method that emphasizes active student engagement in the investigative process to discover new knowledge. This article discusses the concept, models, and application of IBL in enhancing the quality of Islamic Education learning. Using the library research method and qualitative analysis, this study reveals that IBL can improve students' critical, analytical, and reflective thinking skills in understanding Islamic teachings. The implementation of this approach involves several steps, including orientation, problem formulation, hypothesis generation, data collection, hypothesis testing, and conclusion formulation. In PAI learning, IBL enables students to connect religious concepts with real-life situations, making learning more meaningful. Despite challenges such as teacher and student readiness as well as limited facilities, this approach still provides significant benefits for improving the quality of religious education. Therefore, IBL can serve as an effective learning strategy to encourage active student participation and build a more applicable understanding of religious teachings.